Wetlands. - MacEwen, Melissa J. (Tufts Archival Research Center, 2014)
Abstract: What makes the Bay Area of California what it is today? Is it the area's people? Its landscape? Its history? In this chaptered novella, I explore the social and geographic landscapes of this region by telling the story of two Bay Area natives, Eva and James. Once friends, the two begin a romance that doesn’t quite work out, but that probes topics of identity, expectation and gender while exploring the numerous micro-regions of California.